Continuous disclosure compliance: does corporate governance matter?. (4th March 2014) - Chapple, Larelle; Truong, Thu Phuong
Abstract: Our study investigates the quality of firms' continuous disclosure compliance during mandatory continuous disclosure reform, and whether the compliance quality is impacted by corporate governance, using the New Zealand market as the setting. We use a novel coding of different categories of disclosures (non‐routine, non‐procedural and internal), which represents the extent of proprietary insider information inherent in disclosures, to evaluate firms' compliance quality. Our findings provide evidence that firms' compliance quality improved after the reform, and this improvement is inconsistently impacted by corporate governance. Our findings provide important implications for regulators in their quest for a superior disclosure regime.